Phosphorus Fractions in Irrigated and Rainfed Agricultural Soils of Central India - Govind Singh, Alok Kumar, AL. Ramanathan, Anshumali, Kriti Shukla, Bijendra Kumar, Asmaa Naaz, Chandravir Narayan (Journal of the Indian Society of Soil Science, 2016)
Phosphorus (P) fractionation was carried out using sequential extraction method in twenty composite agricultural soil samples to assess the soil fertility of irrigated and rainfed areas around Sidhi district, Central India. The results showed alterations in the biogeochemical relationships between physicochemical parameters. In rainfed areas, the high Si/Al and low Fe/Al ratios showed silicate nature of agricultural soils along with low Fe loss from primary silicates. The relative abundance of P was as follows: Res-P > DNRP > NaOH-Pi > HCl-Pi > HA-P > KCl-Pi. The P content calculated as the sum of different fractions found to have an average variation of Â±1.34% of the total P (TP) obtained by acid digestion. The concentrations of inorganic P fractions were similar in the irrigated and rainfed areas. The organic P was relatively greater in the irrigated soils. The sum of NaOH-Pi, DNRP and Res-P accounted for >70%, while Pi and Po accounted for 55.3 and 43.3% of total P, respectively. The factor analysis revealed that the chemical fractions of P were controlled by pH, clay minerals and oxy-hydroxides.